Kajian Reservoir Leptospira di Daerah Sporadis Leptospirosis - Ningsih, Dewi Puspita; Sholichah, Zumrotus (Media Kesehatan Masyarakat Indonesia, 2018)
Districts in Central Java have been reported as leptospirosis area, one of them is Purworejo. Leptospirosis has been reported in Purworejo since 2005, but less information and reports on rats species and leptospira presence in rats and shrews. This study aims to examine reservoir of leptospira and describe infected serovar in Purworejo.This research was carried out in the Bendosari village Gebang subdistrit, on May until June 2011, and cross sectional study. Data collected by catching and continued by examination of leptospira with MAT. The result shown, that total of rats and shrew were recorded for 30. The most rats and shrew prevalence were recorded about 66,67% of Rattus tanezumi species, catched in house was about 66,67% with female was about 60%. The result of MAT as much 30% rats and shrews infected leptospira with titer >1:40 and infected serovar are L. sarmin, L. semaranga, L. javanica, L. icterohaemorrhagie, L. Patoc and L. Sejroe. House rats and shrews has potentially transmited Leptospira in human.